Team Structures and Academic Values: Gender Differences among Division I Basketball Players - Allen, Michael S. (My University, 1999)
This study utilizes a quantitativeresearch design to assess differences that exist between men and women basketball players with regard to the perceived academic subcultures within their teams. A sample of 656 Division I basketball players completed a Team Socialization Scale, which assessed the socializing influences, that college athletes receive from their coaches and teammates. Results indicated that, despite the increased commercialization and professionalization of women's college basketball, members of women's basketball teams remain significantly more oriented toward academic pursuits than members of men's basketball teams. The two primary variables that differentiated between men and women basketball players were the emphasis placed on the possibility of careers as professional athletes by coaches and teammates. The findings from this study have several practical applications for student athlete support personnel and counselors who interact with student athletes on a regular basis.
Keywords: sex/gender; demographics; academic culture; coaches; basketball